Influence of attitude and behavioral control on Youth Entrepreneurship in Peru (LACCEI, 2024)
The research develops the factors that influence youth entrepreneurs, considering that entrepreneurship is a required and necessary activity in society, the theory of complexity was analyzed for this purpose. The objective was to explain the influence of attitude and behavioral control in youth entrepreneurship in Peru. For this, a quantitative study with a causal design was applied in a sample of 595 students from universities of Peru. The conclusion was that both the attitude and the behavioral control influence positively in youth entrepreneurship, which is why it is important for the progress of the country.